Regressive judgment: implications of a universal property of the empirical world - Fiedler, Klaus; Unkelbach, Christian (Current directions in psychological science, 2014)
In the context of research on human judgment, regression is commonly treated as an artifact or an unwanted consequence of ill-controlled research designs. We ar...
Gesehen am 15.07.2020